Odpowiedzi

2012-08-23T13:28:33+02:00

Brak podanego kwasu, dlatego przykładowo wezmę HCl.

 

2Al + 6HCl ⇒ 2AlCl₃ + 3H₂

___                        _____

2mol            :          3mol

54g              :         6g

3g                :         x = 0.33g

 

 

Mg + 2HCl ⇒ MgCl₂ + H₂

____                        ____

1mol            :           1mol

24g              :           2g

y = 3.96g      :           0.33g

 

 

Odp.: Należy działać np. kwasem solnym na 3.96g magnezu.

 

 

 

 

 

 

 

 

 

 

 

Pozdrawiam :)

9 3 9